How emotional, politically civil and local aspects affect young adults' sustainable consumption in transition economies. Issue 3 (4th May 2017) - Lee, Kaman
ABSTRACT: Sustainable consumption manifolds and mobilizes one's conscious choice to express a politically implied stance on environmental/cultural/social issues, to address social and/or ecological injustices, to reproduce or restore order and justice, as well as to fulfill responsibilities of a citizen consumer. Based on this premise, this paper attempts to explore what sustainable consumption means to young adults in Hong Kong. Findings from three focus groups and six follow-up interviews reveal that Hong Kong young adults' sustainable consumption embeds their political ideals to construct collective civil power to fight against the structural inequalities, market hegemonies, imperial dominance and social/ecological injustice locally. The findings point to the need to further define and refine the unspecified concept of "reflexivity" in existing literature. The paper also unveils how the concept of "sustainable consumption" has evolved from the "individual, " "global, " "rational, " "remotely moral" and "ideological" to the "communal, " "local, " "emotional, " "politically civil" and "actional."